Informality and survival in Ukraine's nuclear landscape: Living with the risks of Chernobyl. Issue 1 (2015) - Davies, Thom; Polese, Abel
Recent debates on informal economic activities have partially switched away from a pure monetary logic towards a more complex one, embedded in long term relations and reckoning with non materialistic paradigms. The role of informality in certain aspects of people's lives has however, remained largely unexplored. This article uncovers what happens when the state retires from (providing benefits and social services to) a geographic area and what kind of mechanisms, practices and institutions are created to make up for this. We suggest that, in the face of de facto abandonment by state welfare, and the absence of a private sector alternative, a myriad of transactions and actors can make up for this by replacing these forms of welfare informally. Our case study focuses on the nuclear landscapes around the Chernobyl Exclusion Zone in north–central Ukraine as we reveal the ways the excluded and abandoned, which we frame as post-nuclear "bare life" (Agamben, 1998), have created a mechanism of social security that is independent from the state and yet complements it. Informal, local and unofficial understandings of nuclear spaces are central to survival in this marginalised and risky environment.